Art as an Investment and the Underperformance of Masterpieces - Mei, Jianping; Moses, Michael (American Economic Review, 2002)
This paper constructs a new data set of repeated sales of artworks and estimates an annual index of art prices for the period 1875-2000. Contrary to earlier studies, we find art outperforms fixed income securities as an investment, though it significantly under-performs stocks in the US. Art is also found to have lower volatility and lower correlation with other assets, making it more attractive for portfolio diversification than discovered in earlier research. There is strong evidence of underperformance of masterpieces, meaning expensive paintings tend to underperform the art market index. The evidence is mixed on whether the law of one price holds in the New York auction market.